Myths about Cuba (Revista História: Debates e Tendências, 2011)
Cuba is not perfect. Blocaded and subjected to the unrelenting harassment and aggression by the most powerful military machine of the history of humanity for five decades cannot avoid suffering from deficiencies, shortages, distortions, inefficiencies and other difficulties. However, since literally 1959, the Cuban revolution has been subjected to a defamation campaign that has managed to embed a demonized depiction of her reality in the brains of millions of innocent consumers of mass media ‘information’. This ‘achievement’ has been repeated for five decades and the essential elements of such a depiction are that the Cuban regime is essentially an obsolete, fossilized, crumbling, totalitarian communist dictatorship headed by a megalomaniac, bloodthirsty tyrant. Such depiction, or varieties of it, contribute to shape public opinion which helps justify US policy against the island and significantly obfuscates ordinary people’s understanding of the complexities of the Cuban revolution, including the almost totality of the enormous amount of positive features of the revolution. His article aims at deconstructing this fallacious though no less powerful mythology that has been constructed about Cuban reality, not an easy task that sometimes reminds us of Thomas Carlyle biographer of Oliver Cromwell, who said he “had to drag out the Lord Protector from under a mountain of dead dogs, a huge load of calumny.” All proportions guarded, it must have been much easier for Carlyle to remove the mountain of dead dogs from the memory of Cromwell that to undo the infinite torrent of calumnies that falls on Cuba, when the object of enquiry is not even yet dead, nor has it fallen into oblivion as it had occurred with the 17th century English revolutionary by the time of Carlyle.Keywords : Cuba – revolution - reality